2007
DOI: 10.1143/jjap.46.995
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field-Induced Strain of Ni–Co–Mn–In Alloy in Pulsed Magnetic Field

Abstract: Medium-density polyethylene (PE) thin films have been successfully prepared by the Langmuir-Blodgett technique. The absorbance obtained by the Fourier transform infrared spectroscopy (FT-IR) measurement was proportional to the number of deposited layers, indicating that the layer-by-layer deposition of PE films proceeded successfully. Using the Kelvin probe surface potential measurement, it was concluded that as-deposited PE films were positively charged due to the displacement of electrons from the film to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…However, as reported by Sakon et al, for NiCoMnIn alloy at about 300 K, the magnetic field hystereses under pulse fields do not differ observably compared with the previous results under steady fields. 11) While for the present NiCoMnAl alloy system, there is still no report of the comparisons up to now, similar to the reports by Sakon et al, the results under pulse magnetic fields may not deviate much from those under steady magnetic fields. Further investigations are still required to experimentally verify this point.…”
supporting
confidence: 74%
“…However, as reported by Sakon et al, for NiCoMnIn alloy at about 300 K, the magnetic field hystereses under pulse fields do not differ observably compared with the previous results under steady fields. 11) While for the present NiCoMnAl alloy system, there is still no report of the comparisons up to now, similar to the reports by Sakon et al, the results under pulse magnetic fields may not deviate much from those under steady magnetic fields. Further investigations are still required to experimentally verify this point.…”
supporting
confidence: 74%
“…Recently, Sakon et al [31] have reported that the same Ni 45 Co 5 Mn 36.7 In 13.3 single crystal shows an almost perfect MMSME for a single magnetic field pulse of 200 Hz, whose characteristic features are similar to those in static magnetic field. 3 alloy in which a compressive pre-strain of about 3 % was applied, where the magnetic field was applied vertically to the compressive axis of the specimen and the length change parallel to the compressive axis was measured.…”
mentioning
confidence: 92%
“…Large MFIS has been observed for Ni 45 Co 5 Mn 36.7 In 13.3 (In13.3). 16,17) After a compressive pre-strain of approximately 3% was applied to In13.3, a steady magnetic field was applied parallel to the compression axis of the sample. The MFIS was measured using the threeterminal capacitance method.…”
Section: Introductionmentioning
confidence: 99%